Spectral Studies for Interaction Between Methyl Orange Dye and Cationic Surfactants in Acetonitrile as co-solvent with Water - Ramadan, M. Sh.; Nabil, G.M.; Elmallah, N.M.; Shaker, A.M. (Asian Journal of Chemistry, 2015)
The interaction between anionic dye methyl orange and various cationic surfactants e.g., n-alkyltrimethylammonium bromide (CnTAB, n = 12, 14 and 16) in different volume % of acetonitrile as co-solvent with water at 25 °C is investigated by spectrophotometric method in a wide scale of concentrations. In this study, we focused on measuring the absorption bands for the above systems below and above the critical micelle concentration of the related surfactant. The maximum absorption below critical micelle concentration is found to decrease by increasing surfactants concentration in the order 0 % > 10 % > 20 % > 30 % acetonitrile. After critical micelle concentration, the absorption is increased and limit of absorption in mixed solvent is higher than in aqueous system due to increase in units of micelles which accept more dye molecules. Binding constant between dye and micelle is found to increase with chain length either in the same solvent or in different mixtures due to mutual influence of electrostatic and hydrophobic forces as the result of varying dielectric constant of the medium. Finally the standard free energy change (DG°) for the binding is observed to be more negative by increasing chain length of the surfactant and volume % of acetonitrile.